Discovery of subcomplete skeletons of mammals (Hyracoidea) in the Palaeogene of Africa (Libya). - (:unkn) unknown (My University, 2004)
Africa is the cradle of a number of major groups of placental mammals but their early record, in the Palaeogene, is extremely scarce and limited to fragmentary fossils. Here we report on exceptionally well preserved, articulated skeletons of a mammal from the lower Oligocene of Libya, which provide a first reconstruction of a Palaeogene hyrax and key information about the primitive skeletal morphology of this endemic African mammal order. Preliminary study indicates that they belong to a single species of Saghatherium, similar in size to S. antiquum. It shows a cursorial and probably digitigrad locomotion.
Keywords: African Research